Hypertextual Information Structures and their Influence on Reading Comprehension: An Empirical Study - Margit Reitbauer (Miscelánea: A Journal of English and American Studies, 2006)
The aim of this empirical study is to evaluate information structures in hypertexts and their effect on reading comprehension. This comparison of how well students comprehend three different structures of hypertext offers new insights into the comprehension process and has the potential to inform the design of websites. In the first section of this paper, the global structure of hypertexts is discussed. In the second section, the subject of navigation within hypertext is related to the theoretical framework of schema theory. The third section describes the empirical study, in which linear, axial and networked hypertexts are used in a series of tests focusing on reading comprehension. The comprehension results are correlated to textual structure and reading time. The results indicate that axial structures are more beneficial to comprehension than networked or linearly arranged hypertext and support the readers’ understanding and memory of content better. The fourth section is devoted to implications for language teaching and outlines several activities for activating learners’ hypertextual schemata. Finally, suggestions for further research and the design of Web pages are made, pleading for displays that combine a record of the user’s path through the document with a map of currently available links.